Marital communication during conflict: a study on attachment dimensions and interaction patterns - Marshina Juliza Mohd Hasim,; Hasrina Mustafa,; Nor Hazlina Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Conflict is increasingly present and could be severe in many adult romantic relationships including marriage, yet understudied in the context of adult attachment style. This study set out to investigate the underlying relationship between adult attachment styles and patterns of interaction in a Malaysian setting. By means of survey method, data was collected using self-reporting questionnaire involving 400 married individuals in the state of Penang, Malaysia for the duration of six months, with Partial Least Squares (PLS) employed for data analysis. The application of Attachment Theory in this study was established via two dimensions of anxiety and avoidance. Result from the analysis yielded all the constructs have composite reliability value of more than 0.6 and convergent and discriminant validity with an average variance extracted (AVE) value greater than 0.50. The findings indicated that, married individuals who are high in anxiety will exhibit destructive and avoidance patterns during conflict. Similarly, married individuals who are high in avoidance will exhibit destructive, avoidance and low level of constructive pattern during conflict. The study concludes that conflict pattern of interaction among married individuals is a function of adult romantic attachment styles. This study also addressed the gap in research literature by providing a non-western context by basing research within a Malaysian setting.